Logistics of Car Rallies on the Example of the Złombol Charity Rally - Karolina ORZEŁ; Monika ZIÓŁKO (Communications of International Proceedings, 2021)
This article raises the subject of logistical organisation of mass events on the example of the Złombol charity rally from the participant's point of view. The aim of this article is to identify barriers to participation in the rally and the usefulness of IT tools improving its course, taking into account additional factors such as respondents’ age or experience in the rally. The first part of this article presents, on the basis of literature, the subject of mass event logistics on the example of rallies. Then, the background of the analysis is outlined, presenting charity rallies in Poland and Europe and the Złombol rally which is the subject of research. In the empirical part, a survey questionnaire was used and the participants of the aforementioned rally were studied in terms of logistical processes at the stage of preparation and participation in the event. The elements examined included the usefulness of the application used during the rally and the identification of obstacles and organisational constraints on participation in the event. The interrelationships between factors were examined based on statistical tests using Statistica and MS Excel software.
Keywords: Charity Rallies; Logistical Processes; Mass Events